Variation in morphological characters of adults of the Aedes (Stegomyia) simpsoni complex from Uganda, Kenya, and South Africa (Diptera: Culicidae) - Lutwama, Julius J.; Mukwaya, L. G. (Mosquito Systematics, 1994)
Examination of adult Aedes simpsoni (Theobald) s.Z. from locations in Uganda and Kenya showed more variation than reported previously. Four patterns of white banding on the midtarsomeres were identified, and they occurred in varying frequencies in samples from different locations. The length of the tarsal bands was distributed continuously within samples from different locations and was variable among progeny of single mothers. This character therefore is not diagnostic of species in the complex. Midtarsomeres 1 and 2 have longer white bands in the majority of males and females of anthropophilic populations in Kenya and Uganda, but there is considerable overlap between the anthropophilic and nonanthropophilic biotypes. A few females in some samples did not bear a tooth on all claws of the fore- or midlegs. Twelve patterns of scutal lines occurred in varying frequencies in samples from different locations. A scutal pattern with long inner lines and short outer lines was most common, with an average occurrence of 5 1.2% in females and 32.2% in males. An H-pattern of scutal lines was more frequent in males (42.1%) than in females (12.10/o), indicating a sex association. Three tergal banding patterns were defined. We conclude that the nominotypical Ae. simpsoni in southern Africa is a distinct species different from the more widespread Ae. Zilii (Theobald) in tropical Africa. Aedes bromeliae (Theobald) cannot be distinguished from the latter based on characters presently described as diagnostic.